Effect Of Sparging In Microalgae (Dunaliella Tertiolecta) Cuture Using Bubble Column - Hadiyanto Hadiyanto; M. Barbosa; R. Wijffels (Reaktor, 2002)
Microalgae as a photosynthetic microorganism that contain chlorophyll has high potential to produce novel high value compounds that can be used in food, pharmaceutical and cosmetic industries. With lack of rigid cell wall, microalgae susceptible to have  hydrodynamic stress by increasing aeration rate. Increasing gas flow rate will increase the productivity to optimum condition, but after this condition the productivity will  decrease due to cell disruption. In this research has been  focused on effect of sparging on  microalgae cell damage. Sparging experiment was carried out by varying gas flow rate between 0.59 to 5.13 L.min-1 with a sparger made from needle inserted to a piece of silicon. The needle was used with diameter 0.4 to 1.2 mm and 1-9 needles. With this variables resulted gas entrance velocity between 2.56-104 m.s-1. The cell death rate constant (kd) was calculated by loss of cell viability in time using Coulter counter and Flowcytometer. From the experiments resulted gas entrance velocity was main cause for cell damagae. The small bubble was more detrimental than bigger size of bubble. Bubble rising as like in animal cell culture was no effect to detrimental cell.Keywords : D. tertiolecta, cell death rate constant, gas entrance velocity